Perancangan Sistem Pengelolaan Limbah Durian Layak Kompos di Agrowisata Kampung Durian Ponorogo - Atika Masrifah; Haris Setyaningrum; Adib Susilo; Imam Haryadi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Ngebel is known as one of the centers for durian fruit in Ponorogo, and is known as Kampung Durian. Durian skin waste that has not been utilized. Through the Asset Based Community Development (ABCD) approach the team of this community service has assisted to make use of durian skin waste to become organic fertilizer to supplements the durian crops. Through the construction of the composter house and technology transfer support program for the processing of durian skin waste into organic fertilizer, the results showed that the people of Kampung Durian village were able to make organic fertilizer with good quality standards. The organic fertilizer products have been tested on durian crops, so that they can increase the production and quality of durian fruit, increase the capacity of the Karang Asri Farmer Group in Kampung Durian to use local resources and increase the capacity to cultivate and process durian skin waste.